2015
DOI: 10.1159/000368767
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo Comparison Study of Smart Shooter®, a New Endoscopic Device for Safe and Speedy Treatment

Abstract: Background: In many endoscopic procedures, the operative view can be compromised when manipulating the treatment device because the endoscopists must release their hand from the endoscope. We have developed a new device called the Smart Shooter® (SS) for simultaneous manipulation of the endoscope and treatment device, and evaluated the utility of the SS compared with the conventional method. Methods: The SS is a semirigid, loop-shaped channel extender that enables endoscopists to manipulate the treatment devic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…There is another way that ESD knives can be manipulated. Kikuchi et al reported the utility of the Smart Shooter, a device that enables endoscopists to manipulate ESD knives using their right thumb while holding the endoscope with their right hand 11 12 . Use of this device, however, requires endoscopists to learn how to control the treatment device with their thumb, which they rarely have a chance to practice.…”
Section: Discussionmentioning
confidence: 99%
“…There is another way that ESD knives can be manipulated. Kikuchi et al reported the utility of the Smart Shooter, a device that enables endoscopists to manipulate ESD knives using their right thumb while holding the endoscope with their right hand 11 12 . Use of this device, however, requires endoscopists to learn how to control the treatment device with their thumb, which they rarely have a chance to practice.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported on the handling of treatment devices while keeping the endoscope in place [14] , but this technique apparently required improvement. To address this issue, we developed the Smart Shooter ® , which allows the endoscopist to manipulate endoscopic devices while continuing to operate the endoscope, and have reported its utility in ex-vivo studies [1,15] . Although the ex-vivo studies were conducted with many limitations, such as not evaluating bleeding or factors affecting manipulation of the endoscope (e.g., respiratory variations and heartbeat), the procedure time was significantly reduced with the use of the Smart Shooter ® compared with conventional methods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although the Dual Knife was used in all cases in this study, we plan to investigate the treatment outcome of the Smart Shooter method when used concurrently with the IT knife and Hook Knife. It is also necessary to investigate its utility not only in ESD, but also in EMR, EIS, peroral endoscopic myotomy, and endoscopic retrograde cholangiopancreatography [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…It is a frequent experience that the layer to be dissected is identified, but the visual field is lost during manipulation of the treatment device. Smart Shooter® has been developed as a solution to these problems [8][9][10]. The objective of this study was to evaluate the usefulness of Smart Shooter® in colorectal ESD.…”
Section: Introductionmentioning
confidence: 99%